Nowy impuls dla kreatywności – uwagi na tle nowelizacji niemieckiego prawa autorskiego z 20.12.2016 r. w zakresie prawa do wynagrodzenia twórców - Giesen, Beata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The reliance between legal guarantee of author renumeration, innovation and creativity of society is nowadays undeniable. This persuasion inspired German legislator for many years. It is conveyd by the series of modifications introduced in German Copyright Law. The latest laws have entered into force, in March 2017. The implemented changes can be presented in the following way: § 32 d of the amended copyright law enables the author to demand information and equips him with the right to be submitted appropriate report on the scope of the use of his piece of work and extent of attained profits from his work. Performers dispose of the same privilege. Discussed entitlement is granted when concluded contract is for pecuniary interest. However, the character of contractually set payment is of no significance. The author can only demand such information, which „normally, as it is customary ”, can be submitted on the scope of his business activity. This material cannot be demanded by one of the authors, whose contribution to the whole work was minor. Raising a claim by the author is also impossible, if such a claim is not eligible due to divers other reasons, as well as when the request for information is unauthorized. Such request is for example unauthorized when the transfer of material could possibly put the other side of the contract at risk of breaching business secrecy. The author can be exclusively stripped of his powers of entitlement only through collective agreements clauses, which are understood as contracts that are not individually concluded. Therefore this concerns contracts, in which authors are represented by an organization, which incorporates the authors operating in their concrete industry. A vital change in comparison with the state before amendment is broadening of group of entities obliged to provide the information requested by the author about the factual scope of use of his piece of work and extent of attained income from his work. This obligation burdens not only the entity with whom the author concluded a licence agreement but also subsequent licencees, i.e. further entities in the licence chain deriving their right from the author, but are not his contractual partners (§ 32 e). Aside from these two groups obliged to supply information, the responsibility has also been imposed on other different entities. These are namely third parties that participate differently in the economic process of work exportation and are not included in the group of licencees (§32 c I Nr 2 of the Copyright Law). § 32 of German Copyright Law equips the author with the right to apply to the court with the demand to change contractually agreed payment. In accordance with this provision, the author can demand to obtain „adequate” remuneration. The amendment of 20th December 2016 signalizes criteria helpful in determining that salary. These are „frequencies” and scope of use. The amendment of the Copyright Act of 200226 introduced an institution known as „collective regulation rates of renumeration for a certain group of authors”. In practice, these previously mentioned collective agreements had not gained popularity. One of the reasons for such behavior was the fact that arrangements made with this procedure were exhibiting the character of recommendations, i.e. they were not binding for partners, which later concluded contracts individually. The amendment of 20 December 2016 keeps this method of determining renumeration of authors, however, it does try to remove its disadvantages. First of all, the time to carry them out was drastically cut. A legal presumption, which allowed to accept a priori that particular associations are entitled to implement the negotiations on behalf of certain group of authors, was introduced. This legal presumption is applicable if the association represents „substantial number” of authors of specific category of pieces of work on the one hand and entities making use of them on the other hand. Despite the above mentioned legal presumption, the association members keep the right to adopt different resolution in this regard. Prefigured term to questioning adopted proposition of height of salaries was also cut. It is currently six weeks27. The copyright law will equip the authors with claim for omission, in case if the other party – entity directly bound with arrangements, breaks previously made arrangements. The latest amendment introduced in § 40a is the so-called right of second use. Its significance is based on the fact that after 10 years from the moment of transferring entitlement to exploitation of work to the holder of an exclusive licence, the right returns to the author. As a consequence, the author again gains the possibility of disposing of this right. The reason for the introduction of the above mentioned solution was a practice known as „Total Bay Outs”- the so-called „sell” complete, which strictly speaking, relies on purchasing licence authorisation just in case for a one-time payment. In order to help the author to break free of this sort of trap, the possibility of demanding the return of the right to use his own piece of work was guaranteed. If the author executes his entitlement, the right of financial exploitation will return to him. What is essential though, the previous licencee is not losing his entitlement to use piece of work. He stops to be an only exclusive licencee. Differently speaking, the exclusive licence transforms into a non-exclusive licence. The law also provides for the possibility of waiving the entitlement by the author. He cannot proceed with that instantly though, but only after five years from the moment of signing a contract.